(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In the present manuscript, we have introduced a new notion of (β, φ)-expansive mappings in controlled metric space. In addition to this, some fixed point results are also proved with the help of this notion. Some results from the literature are also deduced from our main results. An example is also provided to prove the validity of our result. As an application an integral equation is also solved with the help of our main result.